2004
DOI: 10.1038/sj.bjc.6601867
|View full text |Cite
|
Sign up to set email alerts
|

Para-aortic irradiation for stage I testicular seminoma: results of a prospective study in 675 patients. A trial of the German testicular cancer study group (GTCSG)

Abstract: A prospective nonrandomised trial was performed in order to evaluate tumour control and toxicity of low-dose adjuvant radiotherapy in stage I seminoma with treatment portals confined to the para-aortic lymph nodes. Between April 1991 and March 1994, 721 patients were enrolled for the trial by 48 centres in Germany. Patients with pure seminoma and no evidence of lymph node involvement or distant metastases received 26 Gy prophylactic limited para-aortic radiotherapy. Disease-free survival at 5 years was the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 34 publications
(59 reference statements)
5
32
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Three were randomized controlled trials, 9 were phase 2 trials, and 5 were from prospective institutional databases. For purposes of summary data generation, these studies included a total of 5561 patients ( Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Three were randomized controlled trials, 9 were phase 2 trials, and 5 were from prospective institutional databases. For purposes of summary data generation, these studies included a total of 5561 patients ( Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…After inguinal orchiectomy, 3 options for CS1 seminoma patients are available. Traditionally, abdominal radiotherapy was the preferred option because microscopic metastatic spread to the retroperitoneal lymph nodes and may be present despite normal imaging results [6,7,8,9]. Although radiotherapy produces excellent durable cure rates, this management strategy was challenged due to rising concerns over possible long-term toxicities as the induction of second malignancies [10].…”
Section: Introductionmentioning
confidence: 99%
“…47,[50][51][52][53][54][55] In the MRC TE10 trial, the two in-field recurrences occurred in conjunction with pelvic or mediastinal recurrence. 55 The combined analysis found that in those men receiving adjuvant para-aortic field, 37% of the 54 relapses were to the pelvis, 26% to the mediastinum or neck, and 7% to the abdomen alone.…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%